EMPIRICAL RESEARCH OF PSYCHOLOGICAL WELL – BEING OF YOUNG PEOPLE STUDYING AT REZEKNE ACADEMY OF TECHNOLOGY - Kalvans, Eriks (Education Reform: Education Content Research and Implementation Problems, 2021)
This scientific article reflects the results of research on the psychological well-being of students at the Rezekne Academy of Technologies. The need for such research is justified by recent research in various countries, which shows that the prevalence and severity of mental problems among students is increasing. Overall, these studies indicate that students are increasingly experiencing symptoms of increased anxiety and stress, as well as depression. Thus, the deterioration of students' psychological well-being is a major challenge in today's higher education institutions.The aim of the empirical research: to study the content and peculiarities of the psychological well-being of students in relation to certain demographic and social factors.The analysis of scientific literature and empirical results were used as basic methods in the development of the article.